Legal issues of struggle against tuberculosis in Kazakhstan (International relations and international law Journal, 2018)
The paper discloses the problematic aspects of legal regulation of tuberculosis control in the Republic of Kazakhstan and foreign countries. Despite the inception of modern treatments and public health interventions, tuberculosis (TB) remains a significant public  health  threat  in  Kazakhstan  and  abroad  in the twenty-first century. The challenge of controlling TB in its traditional and  new  multidrug-resistant forms requires public health agencies at the high levels to develop and apply new tools. Among these tools is the use of law to support efforts to effectively monitor cases of tuberculosis. The purpose of this article is not to consider all socially significant diseases, but a detailed analysis of the legal regulation of the control of tuberculosis patients in the Republic of Kazakhstan based on international experience. The authors detailed the legal and regulatory framework for the prevention, diagnosis and control of infection with the bacterium Mycobacterium tuberculosis. Also measures of compulsory treatment of patients with tuberculosis, their rights and duties are described. For the disclosure of the topic, the methods of historical research and the system method were used in the article. The article is intended for a wide range of readers interested in medicine, jurisprudence and international attitudes.Key words: The Republic of Kazakhstan, Tuberculosis, prevention, treatment, control.